2022
DOI: 10.3389/fenvs.2021.745498
|View full text |Cite
|
Sign up to set email alerts
|

Does Innovative Development Drive Green Economic Growth in Resource-Based Cities? Evidence From China

Abstract: Seeking innovative development has become a necessity for global cities because of the accelerating consumption of natural resources and the increasing need for urgent control of environmental pollution. However, few studies have reported on the effect of innovative development on the green economic growth of resource-based cities. Therefore, this study aimed to construct the SBM model of unexpected output to measure the efficiency of green economic growth using data of 108 resource-based cities in China from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 110 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Moreover, the agglomeration of firms in different industries is conducive to the collision of technologies between fields which can induce the reform of green technologies. The improvement of firm technology level has improved firm environmental performance (Yi et al, 2022;Zhang et al, 2022). Based on the above analyses, this paper proposes another hypothesis: Hypothesis 2.…”
Section: Theoretical Hypothesismentioning
confidence: 94%
“…Moreover, the agglomeration of firms in different industries is conducive to the collision of technologies between fields which can induce the reform of green technologies. The improvement of firm technology level has improved firm environmental performance (Yi et al, 2022;Zhang et al, 2022). Based on the above analyses, this paper proposes another hypothesis: Hypothesis 2.…”
Section: Theoretical Hypothesismentioning
confidence: 94%
“…A large number of documents have analyzed the development models, policies and paths of industrial transformation and economic transformation in the transformation and upgrading of resource-based cities. Through literature analysis, it can be found that innovation drive is an important factor to realize the transformation and upgrading of resource-based cities, but the efficiency of transformation and upgrading of resource-based cities not only depends on scientific and technological innovation, but also is affected by non-scientific and technological factors such as institutional, policy and management changes [17]. Therefore, it is necessary to consider all aspects of institutions, industries and elements in a comprehensive and multi-level manner to promote the transformation of resource-based cities through integration and interaction.…”
Section: Research Progress On Sustainable Development Of Resource-bas...mentioning
confidence: 99%
“…(1) fiscal level (fiscal): taking into account the crucial role of promotion and support for the government in the development of TI, and the close relations between fiscal revenue and HGD [20], this paper uses the ratio of local government fiscal revenue to GDP in the various cities to measure the level of regional fiscal revenue. (2) Industrial structure (is): in line with the previous study [54], this study selects an indicator reflecting the degree of advanced industrial structure, namely, the ratio of the output values of the tertiary and secondary industries to represent the industry structure. (3) Population size (den): we use the population density of various cities to express the regional population size [20].…”
Section: Controlmentioning
confidence: 99%